Is Kazakhstan vulnerable to natural resource curse? - Yessengali Oskenbayev; Aziz Karimov (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This study utilizes panel data from 14 provinces of Kazakhstan and investigates the link between the point-source resources (oil and gas) and economic growth via institutional quality. Labour force migration from manufacturing to non-traded sector occurs as a result of wage increase in the manufacturing sector while its production price is determined and pinned down by the world market. On top of that, the manufacturing sector costs increase even more as a consequence of the price increase of non-traded goods used as inputs in the manufacturing sector. Although, the impact of interaction terms of diffuse resource (wheat) production and institutional quality is not observed, diffuse resources deteriorate the economic growth through wheat price volatility. The wheat price spikes lead to institutional inefficiencies. Moreover, rent-seeking activities of intermediaries in agricultural sector further undermine the economic growth.
Keywords: E02; Q17; Q18; Q27; 330; energy production; Kazakhstan; point-source; diffuse resources